Biodiesel Production from Waste Cooking Oil - Endang Sri Rahadianti; Yerizam Yerizam; Martha Martha (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
Increased energy consumption and the depletion of petroleum reserves have pushed up oil prices globally. The diminishing petroleum reserves are a problem inherent in this type of fossil energy. One alternative energy source that has the potential to be developed in Indonesia is biodiesel. Used cooking oil or used cooking oil is a potential raw material for making biodiesel. In this study biodiesel was made from used cooking oil and methanol using the transesterification method with KOH catalyst. The production of biodiesel from used cooking oil begins with mixing raw materials of used cooking oil collected into one. The mixture is then precipitated for 24 hours. The transesterification process was carried out by mixing KOH (1% of oil weight) with methanol (ratioof methanol: oil 6: 1) at a temperature of 65 oC. After the temperature is reached, the methanol and KOH solution is added slowly while pumping (stirring), with a variation of time 30, 45, 60.75 and 90 minutes. Biodiesel purification is done by washing using hot water (temperature 70 C) twice as much washing. Characteristics of biodiesel based on the best conditions for density 0.886 g / mL, viscosity 5.89 cSt, FFA 0.11% , acid value 0.256 mgKOH/g and flash point 170.52 oC. The biodiesel products based on these parameters meet SNI 7182-2015 standards.